Pembedayaan Masyarakat Melalui Pemanfaatan Komoditas Ketela di Desa Giricahyo - Sunarsih Sunarsih (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2020)
This paper tries to explore the empowering model through the function of cassava commodity as an increase of prosperous people in Giricahyo Village, Gunungkidul. Through a community-based research approach, qualitatively, a workshop for cassava commodity development has become the trend in the empowerment program. The framework to change the way of positivistic paradigm to shift more than holistic, synergic, and transdisciplinary can be claimed as a new model of social intervention. Furthermore, the study finds that assistance people can be optimized when it is paradigm implemented in the community development process. This article argues that the innovation of cassava processed in various creativity can appear new understood and knowledge for people to restricted productivity. Society has been motivated to open a new enterprise product. However, social welfare can not evaluate in this program. Optimization of cassava processed has become snack produce that it can be a solution of increasing prosperous people with the evaluation of the program.Tulisan ini mengeksplorasi model pemberdayaan melalui pemanfaatan komoditas ketela sebagai upaya untuk meningkatkan kesejahteraan masyarakat Desa Giricahyo, Gunungkidul. Melalui pendekatan community-based research, secara kualitatif, pelatihan pengembangan komoditas ketela menjadi trend dalam program pemberdayaan. Kerangka kerja dari perubahan cara pandang pemikiran positivistik ke arah yang lebih holistik, sinergis, dan transdisipliner dapat diklaim sebagai model intervensi sosial baru. Karena itu, studi ini menemukan pendampingan masyarakat dapat berjalan optimal ketika paradigma tersebut diterapkan dalam proses pemberdayaan. Artikel ini berargumentasi bahwa inovasi olahan ketela dengan beragam varian kreativitas dapat memunculkan pemahaman dan wawasan baru bagi masyarakat dalam produksi yang terbatas. Masyarakat telah termotivasi untuk membuka usaha baru. Namun demikian, tingkat kesejahteraan masyarakat tidak dapat diukur dalam program ini. Pengoptimalan pengolahan ketela menjadi makanan ringan dapat menjadi solusi untuk meningkatkan kesejahteraan dengan capaian evaluasi yang terukur.